A Knowledge Framework for the Philosophical Underpinnings of Research: Implications for Music Therapy. (31st October 2018) - Matney, Bill
Abstract: Current music therapy studies suggest great diversity and complexity in research approaches. Authors note the importance of increased clarity in many facets of research reporting. Some authors have also encouraged increased understanding and reporting of the philosophical underpinnings of knowledge generation in research. However, like other social science fields, we appear to have struggled to provide clear frameworks that can address such diverse and complex approaches to research. In this article, I offer one way to resolve such struggles by presenting a re-envisioned version of Michael Crotty's knowledge framework. I seek to meet this purpose through the following objectives: (a) discuss philosophy and its role in research; (b) detail challenges related to understanding and reporting epistemological underpinnings; and (c) present a modified version of Crotty's knowledge framework to promote understanding and reporting, including visuals, brief examples, and resources. I also re-envision the framework to address potential challenges to typologies and to maintain the spirit of Michael Crotty's work. Modifications promote the dynamic and interactive relationship between and within epistemological positions, theoretical perspectives, methodologies, and methods, while also integrating surrounding factors: research question, researcher, context, and participant. I dialogue with related literature on knowledge generation, show how some recent music therapy research engages with the knowledge framework, discuss methodologies and approaches that may not align with the knowledge framework, offer resources for further reference and learning, and describe implications for researchers, research consumers, and the ongoing body of knowledge.